Efek Residu Kacang Hijau Pertanaman Pertama pada Pertumbuhan dan Hasil Kacang Tunggak Pertanaman Kedua di Lahan Kering - Sri Ayu Dwi Lestari; Sutrisno Sutrisno; Andy Wijanarko; Henny Kuntyastuti (Institut Pertanian Bogor, 2020)
The objective of this research was to determine the residual effect of fertilizer and former plant spacing of mungbean first planting on growth and yield of cowpea second planting in a dry land. The experiment was conducted at Muneng Research Field, Probolinggo, East Java during dry season in 2015. The cowpea seeds of KT 5 varieties were planted in plots measuring 4 m x 4,5 m with plant spacing of 40 cm x 15 cm, 2 plants/hole. This research was carried out without adding fertilizer (fertilizer application only given on mungbean planting). This experiment was laid out in a split plot design and replicated three times. Plant spacing of mungbean as the main plot, namely 1) former of 40 cm x 10 cm, 1 plant/hole (J1); 2) former of 40 cm x 15 cm, 2 plants/hole (J2); and 3) former of 40 cm x 20 cm, 2 plants/hole (J3). Residual combination of organic and inorganic fertilizers as the sub plot, namely 1) former without fertilizer (R0); 2) former of 50 kg ZA + 50 kg SP-36 + 100 kg KCl/ha (R1); 3) former of 150 kg Phonska/ha (R2); 4) former of 5000 kg organic fertilizer/ha (R3); and 5) former of 75 kg Phonska + 2500 kg organic fertilizer/ha (R4). The results showed that the cultivation of cowpea with R3 and R4 treatments had effects on shoot and roots dry weights. The highest cowpea yield was obtained with J3 and R4 treatment of 1,62 t/ha and the highest biomass was obtained with J3 treatment of 5,92 t/ha, but statistically not significantly different from the other treatments. Keywords: cowpea, dry land, residual fertilizer